ANALISIS BUKU SISWA MATEMATIKA KURIKULUM 2013 UNTUK KELAS X BERDASARKAN RUMUSAN KURIKULUM 2013 - Widyaharti, Maulina Syamsu; Trapsilasiwi, Dinawati; Fatahillah, Arif (KadikmA, 2015)
Abstract: In 2013, there were changes of curriculum in Indonesia. The name of new curriculum is 2013 curriculum. The difference of 2013 curriculum is the student book has been provided by The Goverment. Analysis on student book is needed for reviewing the suitability of student book by 2013 curriculum formulation. Analysis was done based on four criteria, that are competence, material, scientific approach and authentic assessment. Research instrument was form of questions that consist of : 11 competence questions, 11 material questions, 10 scientific approach questions, and 8 authentic assessment questions. Analysis result showed the persentage of competence suitability is 80,49% (good categories), for the persentage of material suitability is 81,06% (good categories), for the persentage of scientific approach suitability is 95,83% (very well categories), and the persentage of authentic assessment suitability is 88,80% (very well categories). Keywords: analysis, 2013 curriculum, student book.